(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One of the key epigenetic modifications in the eukaryotic genome is DNA methylation it has been shown to play a role in complex cell-type regulation of gene expression, and thus cell-type identity. The gold standard for calculating methylation across the genomes of interest is bisulfate sequencing. Here, for the study of high-throughput bisulfate sequencing, we examine many techniques used. To guarantee data accuracy, we implement advanced short-read alignment techniques as well as prepost-alignment quality check methods. In addition, after alignment, we address subsequent review steps. We implement different methods of differential methylation and compare their output using datasets of simulated and actual bisulfate sequencing. We also address the techniques used to segment methylomes to classify regulatory regions. We implement methods of annotation that can be used for further classification by segmentation and differential methylation methods of regions returned. Finally, we analyses software packages that incorporate techniques to deal effectively locally with large bisulfate sequencing datasets and address workflows for online research that do not require any previous programming skills. The analysis techniques outlined in this review will direct researchers to the best bisulfate sequencing analysis practices at any stage.